2005
DOI: 10.1097/01.shk.0000176184.51676.89
|View full text |Cite
|
Sign up to set email alerts
|

Oxygent™ as a Top Load to Colloid and Hyperoxia Is More Effective in Resuscitation From Hemorrhagic Shock Than Colloid and Hyperoxia Alone

Abstract: Perfluorocarbon (PFC) emulsions are intravascular oxygen therapeutics that temporarily enhance tissue oxygenation in dilutional anemia. However, PFC emulsions are not resuscitation fluids because PFCs only work optimally in the presence of high O2 partial pressure (hyperoxia); moreover, because they have no oncotic potential, dosing limitations prevent their use to permanently replace large hemorrhage volumes. Our objective was to clarify whether in the presence of hyperoxia a conventional colloid therapy supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In skeletal muscle, PFC improved O 2 transport after hemorrhage . In dogs, PFC increased intestinal mucosal tissue oxygenation and was also successfully used in cardiopulmonary bypass …”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, PFC improved O 2 transport after hemorrhage . In dogs, PFC increased intestinal mucosal tissue oxygenation and was also successfully used in cardiopulmonary bypass …”
Section: Discussionmentioning
confidence: 99%
“…However, the supplementation of conventional shock-therapy (i.e., crystalloids and colloids) with PFC may be advantageous. In splenectomized dogs, Kemming and coworkers demonstrated beneficial effects on survival and tissue oxygenation attributable to the combined use of fluid resuscitation with hetastarch, hyperoxic ventilation, and infusion of 4.5 mL/kg Oxygent™ 60% [47]. The same treatment modality was found beneficial in rats subjected to hemorrhagic shock: hepatic microcirculation, tissue oxygenation, and hepatocellular energy metabolism were restored most sufficiently in PFCtreated animals when compared with colloidal fluid resuscitation alone or with the transfusion of stored RBCs [75,76].…”
Section: Pfcmentioning
confidence: 97%
“…In this regard, a study of combined hyperoxic ventilation with partial fluid resuscitation in a lethal model of porcine hemorrhagic shock reported that supplementation of partial fluid resuscitation with normobaric hyperoxic ventilation improved tissue oxygenation and survival 77 . In addition, combined treatment with fluid resuscitation, perfluorocarbon and NBO was found significantly superior to each of the therapies alone in a severe canine model of hemorrhagic shock 78 . Altogether, sufficient experimental data are available to suggest that hyperoxic ventilation is a valuable adjunct to other commonly accepted modalities currently employed for resuscitation in trauma/shock.…”
Section: Hyperoxic Ventilation In Hemorrhagic Shockmentioning
confidence: 99%